Is hidrorium able to improve the students’ critical thinking skills? - Dedy Dwi Setyawan; Ali Mustadi (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2020)
The condition of the students’ critical thinking skills in the Kowangbinangun State Elementary School has impacted their learning results. Departing from this situation, a study for improving the students’ critical thinking skills and learning results by using hidrorium as the media should be conducted. Within the conduct of the study, the approach that had been adopted was the classroom action research. Then, the instruments that had been implemented were the test instrument, namely the test items for measuring the achievement of the students’ learning results, and the non-test instrument, namely the assignment assessment rubric for measuring the students’ critical thinking skills level. Furthermore, the data analysis method that had been adopted was the descriptive-comparativee method. Within the first cycle, 4% of the students belonged to the “Very High” category, 14% of the students belonged to the “High” category, and 82% of the students belonged to the “Low” category; as a result, 33% of the students met the passing grade while 67% of the students did not meet the passing grade. The research in the first cycle improved the students’ critical thinking skills and thus 14% of the students belonged to the “Very High” category, 57% of the students belonged to the “High” category, and 29% of the students belonged to the “Low” category. Following up the improvement, the learning results of the students showed that 64% of the students met the passing grade whereas 36% of the students did not meet the passing grade. In the second cycle, the students’ critical thinking skills also improved since 86% of the students belonged to the “Very High” category and 14% of the students belonged to the “High” category. Thus, the students’ learning results improved as well with 82% of the students met the passing grade and 18% of the students did not meet the passing grade.